Technical Features and Development Trend of High-voltageIGBT for Rail Transit Traction Application - DING Rong-jun; LIU Guo-you (机车电传动)
According to application requirements of high-voltage IGBT for rail transit traction application, technical characteristics ofIGBT chip and its module were analyzed respectively. IGBTs for the traction application should have higher power density, higher operationtemperature and be more intelligent and reliable in the future thanks to the technology development of IGBT design and process.